Blood Pressure, Sexual Activity, and Dysfunction in Women with Hypertension: Baseline Findings From the Systolic Blood Pressure Intervention Trial (SPRINT). Issue 9 (1st September 2016) - Foy, Capri G.; Newman, Jill C.; Berlowitz, Dan R.; Russell, Laurie P.; Kimmel, Paul L.; Wadley, Virginia G.; Thomas, Holly N.; Lerner, Alan J.; Riley, William T.
ABSTRACT: Introduction: Sexual function, an important component of quality of life, is gaining increased research and clinical attention in older women with hypertension. Aim: To assess the association between systolic blood pressure (SBP) and other variables, and sexual activity and sexual dysfunction in hypertensive women. Methods: Baseline analysis of 635 women participants of a larger randomized clinical trial of 9361 men and women. Main Outcome Measures: Self-reported sexual activity (yes/no), and sexual function using the Female Sexual Function Inventory (FSFI). Results: 452 participants (71.2%) reported having no sexual activity during the previous 4 weeks. The mean (SD) FSFI score for sexually active participants was 25.3 (6.0), and 52.6% of the sample reported a FSFI score ≤26.55 designating sexual dysfunction. In logistic regression models, SBP was not significantly associated with sexual activity (AOR = 1.002; P > .05). Older age (AOR = 0.95, P < .05), and lower education (AOR for < high school vs college degree = 0.29, P < .05) were associated with lower odds of being sexually active, as was living alone versus living with others (AOR = 0.56, P < .05). Higher weekly alcohol consumption was associated with increased odds of being sexually active (AOR = 1.39; P < .05). In logistic regression models among sexually active participants, SBP was not associated with sexual dysfunction (AOR = 1.01; P > .05). Higher depressive symptoms from the Patient Health Questionnaire-9 (PHQ-9) was associated with higher odds of sexual dysfunction (AOR = 1.24, P < .05), as was increased number of physical comorbidities (AOR = 1.25, P < .05). Diuretic use was associated with lower odds of being sexually active in participants with chronic kidney disease (AOR = 0.33, P < .05). Conclusion: Younger age, higher education, living with others, and higher weekly alcohol consumption were significantly associated with higher odds of being sexually active in a sample of middle-aged and older women with hypertension. Increased depressive symptoms and increased physical comorbidities were significantly associated with increased odds of sexual dysfunction. SBP was not significantly associated with sexual activity or sexual dysfunction.